Why do we need indexicals in communication? - O. A. Kozyreva (Омский научный вестник: Серия "Общество. История. Современность")
The article discusses the pragmatics of using indexicals in communication. I consider the thesis of the indispensability of indexicals from natural languages and the idea that indexicals cannot be reduced to other referential expressions such as descriptions and proper names. Usually, the thesis is supported by the role indexicals play in linguistic communication, making it easier for individuals. I criticize this line of argument by pointing out that indexical expressions can complicate communication as well. The reason for that is using indexicals instead of descriptions reduces the accuracy of information communicated in utterances.